Enacted responsiveness and responsiveness as a disposition: leveraging and valuing student thinking - Gehrtz, Jessica R., author; Hagman, Jess E., advisor; Byerley, Cameron, committee member; Mueller, Jennifer, committee member; Gloeckner, Gene, committee member; Speer, Natasha, committee member (Colorado State University. Libraries, 2019)
Over the past few decades there has been increased attention on instructional practices that incorporate and build on student thinking. To effectively implement these practices, it is essential for an instructor to demonstrate responsiveness to student thinking. Although important, responsiveness is not well-understood at the post-secondary level. In this three-paper dissertation, I first use a thematic analysis to analyze twenty-nine articles that discuss constructs related to responsiveness to student thinking from within the K-16 science and mathematics education literature. Results from this analysis shed light on a distinction between responsiveness as a disposition and enacted responsiveness, which is articulated in the definition for responsiveness to student thinking that I propose. To better understand instructional practices that interact with and impact instructor responsiveness, in the second paper I analyze results from an instructional practices survey that was distributed to college calculus instructors at twelve institutions. Results from quantitative analyses highlight categorizations of instructional practice that relate to responsive practices, indicating that responsiveness can occur in both student-oriented and instructor-oriented classes. In the third paper, I investigate instructor responsiveness to student thinking as a disposition (that guides action) and responsiveness to student thinking as an action (the enacted evidence of the underlying disposition), drawing on interview data from eight college calculus instructors. A thematic analysis of the task-based interviews indicated that instructors who exhibited a responsive disposition to their students' thinking enact this through eliciting student thinking, reflecting on student thinking, and responding to student thinking. Further, these instructors view themselves as decision-makers, and thus feel empowered to act on their responsive disposition. The results from this dissertation have implications for researchers interested in teacher growth and professional development providers.
Keywords: responsive disposition; responsiveness; responsive instruction; instructional activities and practices